Aplicação de análise de sobrevivência no estudo da imobilidade tônica e do comportamento de reintegração social de perdizes (Rhynchotus rufescens) - Hata, Milene Elissa [UNESP] (2014)
The study of tonic immobility (TI) and social reinstatement behavior (SRB) can reveal interactions between man-animal and animal-animal. Those interactions reflect on the welfare of captive animals and may result in positively or negatively effects on the production and profitability of production system. Aiming at understanding the level of fear and the manifestation of sociability in red-winged tinamou (Rhynchotus rufescens), the survival analysis was applied to estimate the time in TI and also the time expent to an animal join with its conspecific. For this, redwinged tinamous reared in the Setor de Animais Silvestres – FCAV – Unesp hatched from 2006 to 2010 underwent TI and SRB evaluations. The observations of TI were performed in 539 birds and the results revealed that the effects of year of birth, month, and body weight of the bird at the time the measure of TI were important sources of variation for the time in catatonia; furthermore, birds with higher body weight tended to remain longer in TI. The SRB observations made in 503 birds showed that the older birds spent more time then the younger to join with their conspecific. The random effect of sire was significant (p < 0.05) for TI and the estimated heritability (h2) by Survival Kit software was equal to 0.37. The h2 for SRB was 0.31, however the estimate is supposed to have a high standard error associated with due to the random effect of sire being not significant. The correlation between the predicted breeding values of TI and SRB was 0.0598 (p = 0.1491), evidencing the non existence of common additive genes between these two traits in the studied population. Therefore, selection to decrease the time in TI could be applied on TI, without changing the level of socialization in this population